# Math

posted by .

Find f(a), f(a + h),
and the difference quotient
f(a + h) − f(a)
------------------
h
,
where h ≠ 0.

f(x) = 4 − 6x + 7x2

f(a)=
f(a + h) =
f(a + h) − f(a)
----------------- =
h

• Math -

f(x) = 4 − 6x + 7x2

7(x + h)^2 -6(x+h) +4-(7x^2 -6x +4))/h

7( x^2 xh+ xh + h^2) -6x -6h + 4 -7x^2 +6x -4))/h
(7x^2 +14xh + 7h^2 -6x -6h +4 -7x^2 + 6x -4)/h
(14xh + 7h^2 -6h)/h
h(14x +7h -6)/h
14x + 7h -6
lim(h->0) 14x + 7h -6 = 14x -6

## Similar Questions

1. ### calculus

Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. y2 …
2. ### biology

Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
3. ### mah

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 6x + 7 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
4. ### math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = x^2+7 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
5. ### Math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 17 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
6. ### MAth

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 2/x+5 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
7. ### math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = x/x+6 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
8. ### math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 2x/x-7 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
9. ### Math

Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) ------------------ h , where h ≠ 0. f(x) = 7x^3 f(a)= f(a + h) = f(a + h) − f(a) ----------------- = h
10. ### Mathematics

Simplify the difference quotient [f(x) − f(a]/[x − a] if x ≠ a. f(x) = SQROOT of (x − 27) (Hint: Rationalize the numerator.)

More Similar Questions